Commercialisation Of Public Enterprises In Nigeria: A Study Of The Nigerian National Petroleum Corporation (Nnpc) (Journal of Namibian Studies : History Politics Culture, 2023)
The National Petroleum Corporation (NNPC), has been known for its poor leadership and unprofitability for the past 47 years. This has been attributed to the government’s inability to repair the existing refineries, along with oil theft and pipeline vandalism which continue to hinder the petroleum revenue performance and oblige the country to import most of its refined products. This necessitated the commercialisation of NNPC. This study analysed the provisions of the PIA, which formed the basis for the commercialisation of NNPC. It also examined if the commercialisation of NNPC would boost the Nigerian economy. This study aims to ascertain the preparedness of diverse stakeholders in the country to accept the recent transition of NNPC from being a public entity to a commercialized enterprise. The Liberal and Public Choice theories were adopted. It also adopted a mixed method of data collection and utilized both the explanatory and descriptive survey research design. The findings revealed that the commercialisation policy itself is not a terrible notion, but the issue is more with its implementation. Finally, it recommended that the policy should be judiciously implemented in line with the provisions of the PIA in order to have practical effects on the country's economic independence.